Malignant Melanoma in Children and Adolescents Treated in Pediatric Oncology Centers: An Australian and New Zealand Children’s Oncology Group (ANZCHOG) Study - Ryan, Anne L.; Burns, Charlotte; Gupta, Aditya K.; Samarasekera, Ruvishani; Ziegler, David S.; Kirby, Maria L.; Alvaro, Frank; Downie, Peter; Laughton, Stephen J.; Cross, Siobhan; Hassall, Timothy; McCowage, Geoff B.; et al. (Frontiers in Oncology, 2021)
Objectives Unlike adults, malignant melanoma in children and adolescents is rare. In adult melanoma, significant progress in understanding tumor biology and new treatments, including targeted therapies and immunotherapy have markedly improved overall survival. In sharp contrast, there is a paucity of data on the biology and clinical behavior of pediatric melanoma. We report a national case series of all pediatric and adolescent malignant melanoma presenting to ANZCHOG Childhood Cancer Centers in Australia and New Zealand. Methods A retrospective, descriptive, multi-center study was undertaken to identify patients less than 18 years of age treated for cutaneous malignant melanoma over a twenty-year period (1994 to 2014). Data on clinical characteristics, histopathology, and extent of disease, treatment and follow-up are described. Results A total of 37 cases of malignant melanoma were identified from all of the Australasian tertiary Childhood Cancer Centers. The median age was 10 years (range 1 month – 17 years). Clinically, the most common type of lesion was pigmented, occurring in sixteen (57%) patients, whilst amelanotic was seen in 7 patients (25%). In 11 (27.9%) the Breslow thickness was greater than 4mm. A total of 11 (29.7%) patients relapsed and 90% of these died of disease. Five-year event free survival (EFS) and overall survival were 63.2 (95% CI: 40.6 – 79.1) and 67.7% (95% CI: 45.1 – 82.6) respectively. Conclusion Our data confirms that melanoma is a rare presentation of cancer to tertiary Australasian Childhood Cancer Centers with only 37 cases identified over two decades. Notably, melanoma managed in Childhood Cancer Centers is frequently at an advanced stage, with a high percentage of patients relapsing and the majority of these patients who relapsed died of disease. This study confirms previous clinical and prognostic information to support the early multidisciplinary management in Childhood Cancer Centers, in conjunction with expert adult melanoma centers, of this rare and challenging patient group.